120 children of UMPSA staff participated in Exploring Mathematics Programme - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 21 December 2023 - A total of 120 participants consisting of the children of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) staff participated in the Exploring Mathematics Programme held at both campuses for four sessions starting last Monday.